Effect of SMAW welding current variations on mechanical properties in ASTM A240 grade 304L - Nurdin, Nurdin; Al Fathier, Al Fathier; Maulana, Rizki; Fakhriza, Fakhriza (Journal of Welding Technology, 2025)
Welding current is one of the important parameters in the welding process, because inappropriate currents will result in welding defects in the welded material resulting in reduced weld joints. This study aims to determine the effect of current variations on SMAW welding joints ASTM A240 Grade 304L material on mechanical properties. This study uses ASTM A240 Grade 304L material with variations in welding currents of 80 A, 100 A, and 120 A using SMAW welding and using E308-16 electrodes with a diameter of 3.2 mm. Specimens were tested for chemical composition, visual test, penetrant test, and tensile test. Comparative data of tensile test explained that the highest tensile stress from variations in welding currents of 80 A, 100A, and 120 A was 625.27 MPa using a welding current of 100 A, the highest yield stress is 337.35 MPa, using a welding current of 100 A, and the highest elongation is 38.34% using a welding current of 100 A. From the data from the tensile test results for ASTM A240 Grade 304L material, the results obtained that the material data without welding treatment has the lowest tensile strength compared to with a group of variations in welding current. And the highest tensile strength value is in the 100 A current variation group.